1992
DOI: 10.1073/pnas.89.20.9769
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogenetic inference from saber-toothed cat fossils of Rancho La Brea.

Abstract: A method for the successful extraction of sequestered cellular DNA from 14,000-year-old fossil bones was developed and applied to asphalt-preserved specimens of the extinct saber-toothed cat, Smilodon fatalis. Two distinct gene segments, the mitochondrial gene for 12S rRNA and nuclear FLA-I (the feline class I major histocompatibility complex gene), from three different individual fossil specimens were cloned and sequenced after PCR amplification. Comparison of fossil-derived DNA sequences to homologous region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…Our survey examined two excavation sites. The first site, Pit 91, has yielded thousands of plant and animal fossils and is the richest Pleistocene fossil site in the world (10,16,45). Carbon dating of fossils from the current depth under excavation in Pit 91 fixes their ages in a range from 10,000 to 38,000 years before the present (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our survey examined two excavation sites. The first site, Pit 91, has yielded thousands of plant and animal fossils and is the richest Pleistocene fossil site in the world (10,16,45). Carbon dating of fossils from the current depth under excavation in Pit 91 fixes their ages in a range from 10,000 to 38,000 years before the present (16).…”
mentioning
confidence: 99%
“…The first site, Pit 91, has yielded thousands of plant and animal fossils and is the richest Pleistocene fossil site in the world (10,16,45). Carbon dating of fossils from the current depth under excavation in Pit 91 fixes their ages in a range from 10,000 to 38,000 years before the present (16). The second site, Pit 101, was excavated early last century and was closed in the 1920s, after which the pit was covered with a permanent building as part of a museum display.…”
mentioning
confidence: 99%
“…For example, such analysis has been successfully applied to the study ofthe extinct moa (reviewed in ref. 12), to 14,000-year-old bones of the saber-toothed cat Smilodon (13), and to a 25,000-year-old bone of Equus hemionus (14). In this context, it was tempting to use PCR amplification to sequence the mtDNA control region in the cave bear, in order (i) to determine the relationships between this extinct species and the two recent lineages of the brown bear in Europe and (ii) to test the phylogeny based on paleontological data.…”
mentioning
confidence: 99%
“…For example, the elucidation of the phylogeny of flightless ratite birds such as moas, kiwis, and ostriches, most of which are extinct, has shown that flightlessness has evolved multiple times in the Southern Hemisphere (Cooper et al 1992). Other examples of convergent evolution have been found among extinct marsupial carnivores in Australia and South America (Thomas et al 1989), and DNA from many extinct animals such as cave bears (Hänni et al 1994), giant ground sloth (Höss et al 1996), and the saber-toothed cat (Janczewski et al 1992), to name a few, have been retrieved. Whole genomes from the mammoth (Lynch et al 2015;Palkopoulou et al 2015) and a 700,000-year-old horse (Orlando et al 2013) presage the complete genomes of many extinct species that will be sequenced over the next decade.…”
Section: Extinct Organismsmentioning
confidence: 99%